EFFECTIVENESS TEST OF WOUND PATCH PREPARATIONS OF GOTU KOLA LEAF EXTRACT (Centella asiatica (L.) Urb.) ON INCISION WOUND IN RABBITS - Marini Marini; Nur Azizah; Devin Nur Rohman; Angga Anugra Diputra (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
A wound patch is a dosage form that delivers drugs through the skin to produce systemic effects, with the advantage of controlled drug release. Centella asiatica (L.) Urb.) is widely used to heal incision wounds on the skin. The most important component was asiaticoside, which plays a major role in accelerating wound healing. This  study  was  conducted  to  test  the  effectiveness  of  transdermal  patches  from Centella asiatica (L.) Urb.) against incision  wounds was performed on 5 rabbits divided into different treatment groups, namely group I without treatment, group II wound patch base (negative control), group III plaster (positive control), and groups IV and V, comprising a wound patch of gotu kola leaf extract at concentrations of 16% and 32%, respectively. The data obtained were statistically tested for normality using the Shapiro-Wilk test.  The results showed that the wound patch preparation of 16% gotu kola leaf extract showed  a significant difference (p < 0.05) in wound length reduction compared to the negative and normal controls.  The wound healing time observed at concentrations of 16% and 32% provided wound healing effects. The best effect was observed at a concentration of 16%, with an average wound closure time of 12 days. It can be concluded that gotu kola leaf extract in the form of a wound patch preparation was effective in wound healing. Keywords: Gotu kola leaf extract; incision wound; Wound patch; Effectiveness test